Undead ends : stories of apocalypse - Trimble, S. (Sarah) (Rutgers University Press, 2019)
"Undead Ends is about how we imagine humanness and survival in the aftermath of disaster. This book frames modern British and American apocalypse films as sites of interpretive struggle. It asks what, exactly, is ending? Whose dreams of starting over take center stage, and why? And how do these films, sometimes in spite of themselves, make room to dream of new beginnings that don't just reboot the world we know? Trimble argues that contemporary apocalypse films aren't so much envisioning The End of the world as the end of a particular world; not The End of humanness but, rather, the end of Man. Through readings of The Road, I Am Legend, 28 Days Later, 28 Weeks Later, Children of Men, and Beasts of the Southern Wild, this book demonstrates that popular stories of apocalypse can trouble, rather than reproduce, Man's story of humanness. With some creative re-reading, they can even unfold towards unexpected futures. Mainstream apocalypse films are, in short, an occasion to imagine a world After Man"--